Harmonizing legality with morality in Islamic banking and finance: a quest for maqāṣid al-Sharī‘ah paradigm - Zakariyah, Luqman (2014)

(untitled)
In recent times, scholars on the Islamic Finance Industry (IFI) have been calling for integrating Islamic moral norms with legal theory in the industry. Among reasons for this call are unethical trends in product innovation and execution of the industry. Implementing Islamic banking and financial practices would require adopting their undergirding Islamic legal and moral frameworks. Departing from these foundations of Islamic law could render the activities conducted under its name religiously unacceptable, and thus perhaps philosophically problematic. Many approaches have been put forward to achieve this course. One of the most complex but yet subjective approaches is the quest for maqāṣid al-Sharīʿa.